A struggle for tenure by the "servant class" of Potchefstroom : a study in structural violence (Historia, 2021)
The "servant class" of Potchefstroom intermittently struggled for some measure of security of the right of occupation and the use of urban land. They first relied entirely on the favour of their masters, then seemingly acquired long-term tenure in a native location. However, they were eventually consigned to the mass category of "urban natives" without tenure, initially under British rule after 1903. When accompanying their white masters on their trek from the Eastern Cape, they were never considered citizens of the republic that was to be constituted in the interior or as having any claim to land in town. Thus they lived with their masters on their burgerreg erwe (civil right stands) until 1888, when a native location was created for them, availing them with some basis for claiming security of tenure in an alternative system. However, partly because their claims of security of tenure were contentious when the location was planned and then established, a legal battle ensued between location residents and the local white authority after the South African War. This clash necessitated the appointment of the Feetham Commission in 1905 and the Armstrong Commission in 1907. These two commissions established certain limited and temporary benefits for location residents in Potchefstroom, partly based on their claims as very early residents of the town. This article covers an early and significant instance of the resistance of the "servant class" in southern Africa to the overarching, harsh social and legal structure in which the legitimacy of their tenure of urban land was ruled out.  Die "dienskneg-klas" in Potchefstroom het vir onderbroke tye 'n stryd gevoer om 'n mate van sekuriteit vir die gebruik of selfs net die besetting van dorpsgrond. Eers was hulle slegs aangewese op die goeie guns van hulle meesters, daarna het hulle reg in die lokasie op die oog af verbeter, om net daarna deel te hê aan die lot van alle inwoners van lokasies onder aanvanklike Britse beheer na 1903. Alhoewel hulle hul wit meesters vanuit die Oos-Kaap vergesel het, is hulle nooit as burgers gereken van die republieke wat in die binneland tot stand sou kom nie, en waardeur hulle 'n reg tot dorpsgrond kon bekom nie. Daarom het hulle saam met hul meesters op burgerreg-erwe gewoon tot in 1888, toe 'n lokasie vir hulle tot stand gebring is binne 'n alternatiewe stelsel wat hulle gemeen het aan hulle 'n basis vir bedinging gegee het. Die omstredenheid met betrekking tot die omstandighede waaronder die lokasie gestig is, en wat hulle as reverdiging vir hulle verwagtings beskou het, en die latere teenoorstaande eise, het die aanwysing genoodsaak van die Feetham-kommisie in 1905 en die Armstrong-kommissie in 1907. Hierdie artikel hanteer 'n vroëe en betekenisvolle geval van die weerstand van die "dienskneg-klas" in suider-Afrika teen 'n oorkoepelende en kras sosiale en regstruktuur waarin die legitimiteit tot die gebruik van stedelike grond uitgesluit was.
Keywords: Township; Zuid-Afrikaansche Republiek; Feetham Commission; Potchefstroom